CLINICAL NEUROPSYCHOLOGICAL INDICATORS OF GENERALIZED ANXIETY DISORDERS IN A REMOTE PERIOD OF A MILD CRANIAL BRAIN INJURY (World Bulletin of Public Health, 2024)
The clinical manifestations of the consequences of BMT are manifold, the different variants of their course, the possibility of manifestation, both in the early and in the distant period of BMT determine the need to develop the technology of rehabilitation of this population of patients depending on the leading syndrome. Generalized anxiety disorders dominate the neurological syndrome of the effects of mild TBT.
Keywords: Anxiety; head trauma; neuropsychological readings